Des-acyl ghrelin prevents heatstroke-like symptoms in rats exposed to high temperature and high humidity. (26th February 2016) - Inoue, Yoshiyuki; Hayashi, Yujiro; Kangawa, Kenji; Suzuki, Yoshihiro; Murakami, Noboru; Nakahara, Keiko
Highlights: Des-acyl ghrelin attenuated hyperthermia induced by exposure to high-temperature. Des-acyl ghrelin reduced the heatstroke-associated reactions. Des-acyl ghrelin in plasma increased under high-temperature and high-humidity conditions. Abstract: We have shown previously that des-acyl ghrelin decreases body temperature in rats through activation of the parasympathetic nervous system. Here we investigated whether des-acyl ghrelin ameliorates heatstroke in rats exposed to high temperature. Peripheral administration of des-acyl ghrelin significantly attenuated hyperthermia induced by exposure to high-temperature (35 °C) together with high humidity (70–80%). Although biochemical analysis revealed that exposure to high temperature significantly increased hematocrit and the serum levels of aspartate amino transferase (AST), alanine transaminase (ALT), blood urea nitrogen (BUN), creatinine and electrolytes (Na +, K +, Cl − ), most of these heatstroke-associated reactions were significantly reduced by treatment with des-acyl ghrelin. The level of des-acyl ghrelin in plasma was also found to be significantly increased under high-temperature conditions. These results suggest that des-acyl ghrelin could be useful for preventing heatstroke under high temperature condition.